2021
DOI: 10.1111/hex.13408
|View full text |Cite
|
Sign up to set email alerts
|

‘You have to do what is best’: The lived reality of having a child who is repeatedly hospitalized because of acute lower respiratory infection

Abstract: Introduction: Hospitalization of children is traumatic for children and their families.Little is known about the impact of repeated acute admissions on families, or of these experiences in Indigenous populations and ethnic minorities. This study explores the societal and health experiences for families who have a child under two years of age, admitted to hospitals more than twice for lower respiratory infections.Methods: Underpinned by a reflective lifeworld research methodology, this article presents results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…38 Five studies reported multiple ethnicities at the Level two category. 26,29,31,39,40 Out of the 29 studies, 28 involved Māori children/whānau, while 24 focused on Pacific children/families. Two studies explicitly focused on Māori, 36,41 and only one study had a Pacific-only cohort, 26 although one study used the term 'Polynesian' to describe their combination of Māori and Pacific participants.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Five studies reported multiple ethnicities at the Level two category. 26,29,31,39,40 Out of the 29 studies, 28 involved Māori children/whānau, while 24 focused on Pacific children/families. Two studies explicitly focused on Māori, 36,41 and only one study had a Pacific-only cohort, 26 although one study used the term 'Polynesian' to describe their combination of Māori and Pacific participants.…”
Section: Participantsmentioning
confidence: 99%
“…25 Three of the four qualitative studies reported on the experiences of families whose children had respiratory infections. 27,29,40 The fourth qualitative study 41 captured the whānau and children's perspectives of asthma and asthma management and used drawing lung representations as an interactive and fun way to engage with children. Other studies included a non-randomised study where children either received an intervention or placebo, 44 a case control study that examined the distribution of housing-related risk factors for children with severe acute respiratory infection 45 and a sero-epidemiologic cohort study which captured influenza infection rates by risk group.…”
Section: Study Design and Intervention Elementsmentioning
confidence: 99%